Peri-operative thrombophilia in patients undergoing liver resection for colorectal metastases. Issue 1 (January 2023) - Welsh, Fenella K.S.; Walsh, Caoimhe M.; Chandrakumaran, Kandiah; Rathnaweera, Wasula S.; Roy, Ashok; Needham, Jane; Cresswell, Adrian B.; McVey, John H.; Rees, Myrddin
Abstract: Background: Routine chemical venous thromboembolism (VTE) prophylaxis for liver surgery remains controversial, and often delayed post-operatively due to perceived bleeding risk. This study asked whether patients undergoing hepatectomy for colorectal metastases (CRM) were at risk from VTE pre-operatively, and the impact of hepatectomy on that risk. Methods: Single-centre prospective observational cohort study of patients undergoing open hepatectomy for CRM, comparing pre-, peri- and post-operative haemostatic variables. Results: Of 336 hepatectomies performed October 2017–December 2019, 60 resections in 57 patients were recruited. There were 28 (46.7%) major resections, with median (interquartile range [IQR]) blood loss 150.0 (76.3–263.7) mls, no blood transfusions, post-operative VTE events or deaths. Patients were prothrombotic pre-operatively (high median factor VIIIC and increased thrombin generation velocity index), an effect exacerbated post-hepatectomy. Major hepatectomies had a significantly greater median drop in Protein C, rise in Factor VIIIC and von Willebrand Factor, versus minor resections (p = 0.001, 0.005, 0.001 respectively). Patients with parenchymal transection times greater than median (40 min), had significantly increased median (IQR) PMBC-TFmRNA expression [1.65(0.93–2.70)2ddCt], versus quicker transections [0.99(0.69–1.28)2ddCt, p = 0.020]. Conclusions: Patients with CRM are prothrombotic pre-operatively, an effect exacerbated by hepatectomy, particularly longer, complex resections, suggesting chemical thromboprophylaxis be considered early in the patient pathway.